The Role of Career Guidance in Strengthening Link and Match in Vocational Education: A Systematic Literature Review - Aditia Gustiana Gunawan; Rina Rifqie Mariana; Tuwoso; Hary Suswanto; Irham (Indonesian Scientific Publication, 2026)
Persistent skills mismatches and prolonged school-to-work transitions among vocational education and training (VET) graduates, intensified by Industry 4.0, highlight the need for stronger alignment between VET systems and labor market demands. Career guidance has emerged as a key institutional mechanism supporting employability and workforce readiness. However, its integrative role in linking educational outcomes with labor market needs remains insufficiently synthesized. This study systematically reviews how career guidance in VET is conceptualized, implemented, and evaluated in relation to employability. Using PRISMA guidelines, a systematic literature review was conducted across Scopus, ScienceDirect, SpringerLink, ERIC, and Google Scholar, yielding 41 peer-reviewed articles. Thematic synthesis shows that career guidance functions as an integrated mechanism enhancing employability, career adaptability, and workforce readiness. Key approaches include Work-Integrated Learning, competency-based frameworks, and digital career guidance platforms, which improve career awareness and alignment with labor market needs. Challenges identified include limited institutional capacity, insufficient expertise, technological disparities, and weak labor market information systems. The study integrates Human Capital Theory, Social Cognitive Career Theory, and Career Construction Theory within a lifelong learning perspective to explain the multidimensional role of career guidance. These findings offer policy and practical insights for strengthening career guidance systems to support sustainable workforce development in the digital economy